The North Sea and Svalbard Fisheries Management Regimes in the Context of Brexit: Divergence and Implications - Yitong Chen; Yinan Wang (Fishes, 2022)
The North Sea fishery has maintained sound and stable cooperative management over the past four decades. European Union (EU) countries exchange quotas with Norway for fish stocks in their respective fisheries jurisdictions within the framework of the EU Common Fisheries Policy (EU CFP) and the Agreement on Fisheries between the European Economic Community and the Kingdom of Norway. After beginning the Brexit process with a concomitant transitional arrangement, the United Kingdom remained in the EU CFP until the end of 2020. From 2021 onward, the United Kingdom became a completely independent coastal state outside the EU CFP framework. In this context, the long-standing and stable fisheries access and quota exchange system between Norway and the EU will face tensions. The differences among the United Kingdom, the EU and Norway in fisheries also involve quotas and access to the Svalbard Protection Zone. Norway even intends to expand the fisheries conflict to the Arctic Council. To prevent the adverse consequences of conflict spillover and to achieve sustainable development of fisheries and win–win cooperation in fisheries management, the United Kingdom, the EU and Norway launched a series of actions on fisheries issues. In tripartite negotiations, each party has its advantages. Ultimately, win–win cooperation in the fisheries game is the three parties’ expected outcome.